Digital tool integration, biodiversity, and potato value chain in Kenya: Baseline evaluation survey report - Boukaka, Sedi Anne; Geoffrey, Baragu; Azzarri, Carlo (International Food Policy Research Institute, 2025)
Potato farmers in Kenya grapple with various challenges across the value chain, including limited access to quality planting material such as seeds and fertilizers, resulting in decreased yields and inferior crop quality; insufficient storage and post-harvest handling facilities, which contribute to high levels of postharvest losses exacerbated by factors such as inadequate transportation infrastructure and pest and disease infestations; fluctuating market prices and limited access to reliable market information systems, leaving farmers vulnerable to income instability. These challenges are further exacerbated for women and youth due to the persistent social gaps in the agricultural sector.